Discovering Craft Villages in Vietnam : Ten itineraries around H - Nicholas Stedman (IRD Éditions, 2016)
With their festivals and traditional industries, their commun halls, pagodas, temples, and vernacular buildings, the villages around Hà Nội possess a rich body of cultural, architectural and craft heritage. Less than one hour from the capital are over 500 specialist craft villages, producing an array of religious or artistic objects, as well as food products, industrial goods, textiles, basketware and much more. Despite the trials and tribulations Vietnam has endured, these traditions have remained alive; today they constitute the basis of material, social and spiritual culture among the village communities of the Red River delta. The artisans themselves, and their local institutions, see cultural tourism as a way of further improving the fortunes of the craft village communities and bringing their heritage to wider attention. Until recently, few guides or tourists had forayed into these settlements, some of which are lost in the maze of routes and tracks that criss-cross the rice paddies of the Hà Nội hinterland. The history and skills they harbour have been inaccessible to all but a few specialists. Few of the villages are signposted, yet between them they are home to three quarters of the architectural, religious and craft heritage of the upper delta. This book, the fruit of several years' research by specialists working in northern Vietnam, comprises ten itineraries, blending potted histories, legends, descriptions of craft techniques, signposted walks and maps, designed to introduce travellers and lovers of Vietnamese culture to forty or so villages around Hà Nội. Many of us have seen their wares on sale in shops in and around the 36 streets of Hà Nội Old Quarter or in other cities in West. This book is about the true lives and enduring skills of the nameless artisans who made them.